Evaluasi dalam Pendidikan Islam - Sari, Lia Mega (Universitas Islam Negeri Raden Intan Lampung, 2018)
Islamic education is used as an ideal goal to be achieved in programs and processes in Islamic products or Islamic educational outputs, and to find out the achievements made by the evaluation activities. With evaluation, it can be called or called the level of progress. But the system used for education is the same as the evaluation system used by general education. Therefore the writer will discuss about evaluation in Islamic education that can be found if it is in it. In this discussion the author uses literature studies to be able to understand education in Islam, the author seeks various references both primary and secondary about studies in Islamic education. The result of this experiment is that the evaluation applied in Islamic education is different from that in general education. That is, if in Islamic education objects that are valued or discussed by students are not just things related to science, nor are they related to religious behavior alone; But the balance between the two. Students are evaluated about religious, social, scientific level, skills and so on. While evaluation in general education is not related to evaluating religious behavior, but the morals are only focused on knowledge, skills or matters relating to student achievement.